Inhumans [videorecording (DVD)] - Ward, Brian (Producer); Jenkins, Paul, 1965-; Lee, Jae, 1972- (Marvel Knights., 2013)
With the city of Attilan under attack from without and within, the fate of an entire civilization rests on the shoulders of Black Bolt, leader of the secretive and extraordinary Inhumans. The Inhumans are led by their king Black Bolt, and his Royal Family, consisting of Medusa, Karnak, Gorgon, Triton, Crystal, Maximus the Mad, and the canine Lockjaw. Both Crystal and Medusa have been members of the Fantastic Four; Crystal has also been a member of the Avengers.